Pengembangan Klub Bahasa di Pondok Pesantren Darunnajah: Analisis Tantangan dan Strategi Peningkatan Keterampilan Berbahasa Arab - Imam Khairul Annas (Jurnal Pengabdian Masyarakat (Bisma), 2024)
This study aims to evaluate the effectiveness of the Language Club extracurricular activity in enhancing Arabic language skills among students at Darunnajah Islamic Boarding School. Through participant observation and in-depth interviews, this study describes various activities offered by the club, such as Ilqo Mufrodat, Muhadatsah, and Ta'lim Lughah. Additionally, this study identifies the challenges faced in implementing the program, such as lack of motivation, limited resources, and individual differences in abilities. The research results indicate that the Language Club has great potential to improve students' Arabic language skills. However, there is a need for more systematic efforts to address the existing challenges. This study provides recommendations for developing more effective programs, including increasing learning motivation, optimizing resource utilization, and differentiating instruction.